2004
DOI: 10.1590/s1516-31802004000600003
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up evaluation of children with birth weight less than or equal to 2,000 g

Abstract: Socioeconomic conditions, clinical/obstetric events and newborn diseases during the hospital stay had repercussions on these children's progress during their first year of life. Their growth profile was found to be very far from the reference standard, thus indicating a need for constant, differentiated assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
(6 reference statements)
1
2
0
Order By: Relevance
“…Our finding of upper respiratory tract infections as the commonest illness persisting throughout the first year of life, followed by diaper rashes, infantile colics, among other morbidities is similar to the reports of Frietas, et al, in Brazil who also noted respiratory tract infections as the most prevalent diagnosis in outpatient visits during the first year of corrected age [17]. Mah, et al, in Yaounde also had comparable findings with respiratory tract infections being most common causes of re-admissions [18].…”
Section: Discussionsupporting
confidence: 91%
“…Our finding of upper respiratory tract infections as the commonest illness persisting throughout the first year of life, followed by diaper rashes, infantile colics, among other morbidities is similar to the reports of Frietas, et al, in Brazil who also noted respiratory tract infections as the most prevalent diagnosis in outpatient visits during the first year of corrected age [17]. Mah, et al, in Yaounde also had comparable findings with respiratory tract infections being most common causes of re-admissions [18].…”
Section: Discussionsupporting
confidence: 91%
“…Martins-Celini et al [15] (2018) did a similar study and reported that in LBW babies gained a mean birth weight of 1.21 kg at 2.5 months and the difference was statistically significant. Freitas M et al [16] (2004) reported that the mean difference between weight at 1.5 months and weight at 2.5 months was 1.238 kg and difference between length at 1.5 months and length at 2.5 months was 3.121 cm. The mean difference Head Circumference at 2.5 months was 0.901cm [16].…”
Section: Discussionmentioning
confidence: 99%
“…Freitas M et al [16] (2004) reported that the mean difference between weight at 1.5 months and weight at 2.5 months was 1.238 kg and difference between length at 1.5 months and length at 2.5 months was 3.121 cm. The mean difference Head Circumference at 2.5 months was 0.901cm [16].…”
Section: Discussionmentioning
confidence: 99%